Gathered in death: archaeological and ethnological perspectives on collective burial and social organisation - Schmitt, Aurore; Dédérix, Sylviane; Crevecoeur, Isabelle (Aegis, 2018)
This volume addresses the topic of collective burial practices, focusing on two main questions: "Who are the deceased buried together in collective tombs?" and?Why are these deceased buried collectively?? Archaeologists, ethnologists and ethnoarchaeologists examin case studies from antiquity to nowadays. Lire la suite00This volume comprises the proceedings of an international workshop that took place at the UCLouvain in Belgium on the 8th and 9th of December 2016. This workshop addressed the topic of collective burial practices, focusing on two main questions: "Who are the deceased buried together in collective tombs?" and?Why are these deceased buried collectively?? Archaeologists, ethnologists and ethnoarchaeologists were thus invited to discuss the identity of the deceased deposited in collective burial places, as well as the ideological and social motivations for gathering the dead in the same tomb over several generations. The chapters in the volume examine case studies ranging from contemporary Madagascar and Austronesia to the Prehistoric Mediterranean and Dynastic Europe. They also reinitiate discussions regarding the potential of archaeological and anthropobiological datasets to approach social organization among past populations.0
Keywords: Konferenzschrift -- 2016 -- Louvain-la-Neuve; Geschichte; Sozialstruktur; Ethnologie; Archäologie; Mehrfachbestattung; Grab; Altertum